An Investigation of Phonetics Instruction in Acquiring English Pronunciation Amongst Polytechnic Learners Using Questionnaires - Mohd Nazri, Latiff Azmi; Regina Lim, Swee Kim (2013)
This study examines the acquisition of pronunciation amongst Polytechnic Kuala Terengganu learners. Quantitative research was conducted via questionnaire administration. Descriptive statistical analysis was used to assess the students’ responses to the learning of phonetics in improving pronunciation. This article focuses on the aspect of mother tongue interference and which English language to speak as gleaned from the results of the questionnaires.